Determinasi Pajak, Mekanisme Bonus, dan Tunneling Incentive terhadap Keputusan Transfer Pricing pada Emiten BEI - Saifudin Saifudin; Septiani Putri (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
This study aims to determine the effect of taxes, bonus mechanism, and tunneling incentive to transfer pricing decisions. Dependent Variables used in this research is transfer pricing and Independent Variables used in this study is the tax bonus mechanism, and tunneling incentive.The population in this study are all companies listed in Indonesia Stock Exchange except for those engaged in the field of finance. The sample selection using purposive sampling method with a final sample of 140 observation period of 2012-2015. The data used is taken from the secondary financial statements of the company. Data analysis techniques used in this study is the technique of logistic regression analysis. With the help of SPSS program application. The results showed that the variables and tunneling tax incentive does not affect tehadap transfer pricing decisions, whereas a variable bonus mechanism of influence on transfer pricing decisions. The coefficient of determination in this study amounted to 13.4%. Future studies are expected to add another independent variable such as an arm's length.